Synergistic effect of ethno medicinal plants against biofilm forming Streptococcus pyogenes isolated from upper respiratory tract infection - MANIMEKALAI KANAGARAJAN; TEEPICA PRIYA DARSINI DEIVAMARUDACHALAM; SRINIVASAN PONNURAJ; DINESHBABU JAGANATHAN (International Journal of Phytomedicine, 2016)
The present study is an attempt to determine the synergistic anti-biofilm efficacy of three Indian medicinal plants namely Ocimum tenuiflorum, Plectranthus amboinicus, and Tylophora indica (OPT) against the biofilm forming Streptococcus pyogenes of upper respiratory tract infection. The leaves were collected and subjected to methanol extraction. The combined extract (OPT) was subjected to preliminary phytochemical and GC-MS analysis. About, ten isolates of S. pyogenes were obtained from the throat swabs samples and studied for biofilm forming potential. The strong biofilm forming isolates were subjected to Minimal Inhibitory Concentration (MIC), Biofilm Inhibitory Concentration (BIC) assays and light microscopic analysis the biofilm inhibition. The results of GC-MS revealed the presence of 39 biologically active phyto-compounds attributed the medicinal properties. The MIC and BIC assay results OPT extracts exhibited anti-biofilm activity at minimal concentration ranging from 0.0156 mg/ml to1.0 mg/ml. Further, the microscopic observations confirmed the altered biofilm architecture of S. pyogenes treated with OPT extract. The findings expound the sturdy synergistic anti-biofilm efficacy of the OPT against biofilm forming S. pyogenes.